Предмет: Алгебра, автор: matuhinandrei19

упростить 3y(x+y+c)-3y (x+y-c)​


pristalovrustam: 3y(x+y+c)-3y(x+y-c)=3y((x+y+c)-(x+y-c))=3y(x-x+y-y+c+c)=3y(2c)=6cy.

Ответы

Автор ответа: fightzoooooor13
0

Ответ:

3x(x+y+c)-3y(x-y-c)-3c(x+y-c)=3x^2+3xy+3xc-3xy+3y^2+3yc-3cx+3cy+3c^2=

=3x^2+3y^2+3c^2

Объяснение:


pristalovrustam: 3y(x+y+c)-3y(x+y-c);
Автор ответа: Andrey9340
1

Ответ:

6yc

Объяснение:

3y(x+y+c)-3y (x+y-c)= 3xy+(3y^2)+3yc-3xy-(3y^2)+3yc=6yc

Похожие вопросы
Предмет: Математика, автор: zekhraalibaeva